Theory of optical responses in clean multi-band superconductors - Junyeong Ahn; Naoto Nagaosa (Nature Communications, 2021)
The optical response of a clean momentum-conserved conventional superconductor is known to be forbidden. Here, Ahn and Nagaosa propose three conditions that intrinsic optical excitations can occur in clean multi-band superconductors by satisfying one of the three.